2023
DOI: 10.3389/fphys.2023.1244279
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of cognitive function tests to acute hypoxia in healthy subjects: a systematic literature review

Titiaan E. Post,
Laurens G. Heijn,
Jens Jordan
et al.

Abstract: Acute exposure to hypoxia can lead to cognitive impairment. Therefore, hypoxia may become a safety concern for occupational or recreational settings at altitude. Cognitive tests are used as a tool to assess the degree to which hypoxia affects cognitive performance. However, so many different cognitive tests are used that comparing studies is challenging. This structured literature evaluation provides an overview of the different cognitive tests used to assess the effects of acute hypoxia on cognitive performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The results suggest that these constructs, when combined with the visual and attentional demands of visual search, were particularly vulnerable to the hypoxia exposure. Other studies have also found adverse impacts of hypoxia on working memory (Malle et al, 2013;Bouak et al, 2018) and Word-Color Stroop performance (Asmaro et al, 2013;Ochi et al, 2018;Post et al, 2023). Future research could investigate further the impact that hypoxia has on higher level cognitive abilities, such as executive function, by utilizing an ERP paradigm that indexes those processes specifically.…”
Section: Discussionmentioning
confidence: 93%
“…The results suggest that these constructs, when combined with the visual and attentional demands of visual search, were particularly vulnerable to the hypoxia exposure. Other studies have also found adverse impacts of hypoxia on working memory (Malle et al, 2013;Bouak et al, 2018) and Word-Color Stroop performance (Asmaro et al, 2013;Ochi et al, 2018;Post et al, 2023). Future research could investigate further the impact that hypoxia has on higher level cognitive abilities, such as executive function, by utilizing an ERP paradigm that indexes those processes specifically.…”
Section: Discussionmentioning
confidence: 93%